Retrovirus Packaging Cells Expressing the Mus dunni Endogenous Virus Envelope Facilitate Transduction of CHO and Primary Hematopoietic Cells - Wolgamot, Greg (American Society for Microbiology, 1998)
Mus dunni endogenous virus (MDEV) infects a wide variety of cell types from many different species. To take advantage of this broad host range, we have constructed packaging cells (PD223) that produce virions bearing the MDEV envelope. PD223 cells are able to package Moloney murine leukemia virus-based vectors at a titer of 4 × 10(5) infectious units per ml in the absence of contaminating replication-competent retrovirus. Vectors packaged by PD223 cells are able to transduce CHO cells, which are resistant to transduction by many retroviruses, at ≥25-fold higher efficiency than vectors having other pseudotypes. A vector packaged by PD223 was found to be among the most efficient for transducing primary baboon and human CD34(+) cells.